The Effectiveness of Teaching Resilience Skills on Family Resilience in Women - Dehghan, Fateme (International Journal of Education and Cognitive Sciences, 2022)
Life in today's world is full of stress and challenges that people have to use the right skills to deal with stressful situations and crises. The purpose of this study is to investigate the effectiveness of teaching resilience skills on family resilience in women. This is a semi-experimental research of pre-test-post-test type with experimental and control groups. The statistical population was 25-50% of the wives of veterans in Kermanshah city in 1402, and 40 women who scored low in resilience were randomly assigned to two experimental (20 people) and control (20 people) groups. The experimental group was trained in resilience skills for 12 sessions, one session per week, and no intervention was done on the control group. Analysis of covariance test was performed to analyze the data. The average age of the participants was 35.48 ± 6.83. The results of covariance analysis showed that there was a significant difference between the average family resilience in the post-test of the experimental group and the control group at the level of p